Challenges of communication in a context of crisis : troubles, misunderstandings and discords - Resende, José Manuel; Martins, Alexandre Cotovio; Breviglieri, Marc; Delaunay, Catarina (Cambridge Scholars Publishing, 2018)
This book questions the political tools and the basis upon which the values of an informed and objective communication rest, and that nowadays encompass most of the ordinary situations encountered in institutions. What is the fate of the involuntary drifts of communication, such as disturbances, misunderstandings and troubles, in the use of decision-making tools, participatory mechanisms, and the establishment of contractual procedures or informed consent practices? How do they open a discordant and potentially critical gap in the protocols and assessment and categorization measures that gover.